Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure! Let's go through the process of simplifying each expression step-by-step.
### Simplifying [tex]\(4^{-\frac{3}{2}}\)[/tex]
1. Understanding the exponent: The exponent [tex]\(-\frac{3}{2}\)[/tex] can be broken into the product of two separate exponents.
[tex]\[ 4^{-\frac{3}{2}} = \left(4^{\frac{1}{2}}\right)^{-3} \][/tex]
2. Calculate the first step: [tex]\(4^{\frac{1}{2}}\)[/tex] is equivalent to the square root of 4.
[tex]\[ 4^{\frac{1}{2}} = \sqrt{4} = 2 \][/tex]
3. Apply the negative exponent: Now raise 2 to the power of [tex]\(-3\)[/tex].
[tex]\[ \left(2\right)^{-3} = \frac{1}{2^3} = \frac{1}{8} \][/tex]
Thus, we have:
[tex]\[ 4^{-\frac{3}{2}} = 0.125 \][/tex]
### Simplifying [tex]\(\left(\frac{1}{16}\right)^{-\frac{5}{4}}\)[/tex]
1. Understanding the base and exponent: The negative exponent indicates a reciprocal. So:
[tex]\[ \left(\frac{1}{16}\right)^{-\frac{5}{4}} = 16^{\frac{5}{4}} \][/tex]
2. Breaking down the exponent: The exponent [tex]\(\frac{5}{4}\)[/tex] can be written as [tex]\(1.25\)[/tex], which is also [tex]\(\left(16^{\frac{1}{4}}\right)^5\)[/tex].
3. Calculate intermediate steps: First, find [tex]\(16^{\frac{1}{4}}\)[/tex].
[tex]\[ 16^{\frac{1}{4}} = \sqrt[4]{16} = 2 \][/tex]
Since [tex]\(2^4 = 16\)[/tex].
4. Raise the intermediate result to the power of 5:
[tex]\[ 2^5 = 32 \][/tex]
Thus, we have:
[tex]\[ \left(\frac{1}{16}\right)^{-\frac{5}{4}} = 32.0 \][/tex]
So, the simplified forms of the given expressions are:
[tex]\[ 4^{-\frac{3}{2}} = 0.125 \][/tex]
[tex]\[ \left(\frac{1}{16}\right)^{-\frac{5}{4}} = 32.0 \][/tex]
### Simplifying [tex]\(4^{-\frac{3}{2}}\)[/tex]
1. Understanding the exponent: The exponent [tex]\(-\frac{3}{2}\)[/tex] can be broken into the product of two separate exponents.
[tex]\[ 4^{-\frac{3}{2}} = \left(4^{\frac{1}{2}}\right)^{-3} \][/tex]
2. Calculate the first step: [tex]\(4^{\frac{1}{2}}\)[/tex] is equivalent to the square root of 4.
[tex]\[ 4^{\frac{1}{2}} = \sqrt{4} = 2 \][/tex]
3. Apply the negative exponent: Now raise 2 to the power of [tex]\(-3\)[/tex].
[tex]\[ \left(2\right)^{-3} = \frac{1}{2^3} = \frac{1}{8} \][/tex]
Thus, we have:
[tex]\[ 4^{-\frac{3}{2}} = 0.125 \][/tex]
### Simplifying [tex]\(\left(\frac{1}{16}\right)^{-\frac{5}{4}}\)[/tex]
1. Understanding the base and exponent: The negative exponent indicates a reciprocal. So:
[tex]\[ \left(\frac{1}{16}\right)^{-\frac{5}{4}} = 16^{\frac{5}{4}} \][/tex]
2. Breaking down the exponent: The exponent [tex]\(\frac{5}{4}\)[/tex] can be written as [tex]\(1.25\)[/tex], which is also [tex]\(\left(16^{\frac{1}{4}}\right)^5\)[/tex].
3. Calculate intermediate steps: First, find [tex]\(16^{\frac{1}{4}}\)[/tex].
[tex]\[ 16^{\frac{1}{4}} = \sqrt[4]{16} = 2 \][/tex]
Since [tex]\(2^4 = 16\)[/tex].
4. Raise the intermediate result to the power of 5:
[tex]\[ 2^5 = 32 \][/tex]
Thus, we have:
[tex]\[ \left(\frac{1}{16}\right)^{-\frac{5}{4}} = 32.0 \][/tex]
So, the simplified forms of the given expressions are:
[tex]\[ 4^{-\frac{3}{2}} = 0.125 \][/tex]
[tex]\[ \left(\frac{1}{16}\right)^{-\frac{5}{4}} = 32.0 \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.